2017
DOI: 10.1016/j.annemergmed.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Do Inhaled Anticholinergic Agents in Addition to β-Agonists Improve Outcomes in Acute Asthma Exacerbations?

Abstract: Comparison of outcomes between combination therapy and b-agonist alone. Outcome Number of Studies (Number of Participants) RR (95% CI) MD (95% CI), % I 2 , % Hospitalization 16 (2,120) 0.72 (0.59-0.86) 12 % Change PEF 7 (551) 24.88 (14.83-34.93) 23 Relapse rates 5 (1,180) 0.8 (0.66-0.98) 0 Adverse events 11 (1,392) 2.03 (1.28-3.02)* 14 RR, Relative risk; CI, confidence interval; MD, mean difference; PEF, peak expiratory flow. *Odds ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Severe exacerbations may occur in patients with mild or well controlled asthma [59,60]. However, poor asthma control is an independent risk factor for future acute exacerbations [61,62,63,64,65]. A history of a recent exacerbation is the strongest predictor of future exacerbations in children and adults with asthma [66,67,68,69].…”
Section: Risk Factors For Asthma Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe exacerbations may occur in patients with mild or well controlled asthma [59,60]. However, poor asthma control is an independent risk factor for future acute exacerbations [61,62,63,64,65]. A history of a recent exacerbation is the strongest predictor of future exacerbations in children and adults with asthma [66,67,68,69].…”
Section: Risk Factors For Asthma Exacerbationsmentioning
confidence: 99%
“…It is not recommended to use anticholinergics as a single therapy for acute asthma. It has been demonstrated that the addition of inhaled ipratropium bromide to therapy with SABAs improve hospitalization rates, relapse rates and are associated with lung function improvement [62,63,64]. This combination therapy benefit is greater for the patients who present with acute severe asthma and are at a higher risk of hospitalization.…”
Section: Pharmacological and Non-pharmacological Managementmentioning
confidence: 99%